2007
DOI: 10.1007/s10551-007-9520-3
|View full text |Cite
|
Sign up to set email alerts
|

Irresponsible Lending? A Case Study of a U.K. Credit Industry Reform Initiative

Abstract: Banking, Borrowing, Credit, Ethics, Lending, Responsibility, Stakeholders,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Taking into consideration recent experiences with irresponsible lending leading to high levels of personal lending via credit cards (Richards et al 2008), which was further exacerbated by the subprime lending upheaval (Gilbert 2011), have all left their mark, and were part of the reasons for the emergence of alternative crowdlending channels. However, these problems were created by individuals who failed in their moral duties when making decisions that later led to significant harmful consequences from default and bankruptcy and all the way to suicide (Gilbert 2011;Richards et al 2008).…”
Section: Ethical Considerations In Crowdlendingmentioning
confidence: 99%
“…Taking into consideration recent experiences with irresponsible lending leading to high levels of personal lending via credit cards (Richards et al 2008), which was further exacerbated by the subprime lending upheaval (Gilbert 2011), have all left their mark, and were part of the reasons for the emergence of alternative crowdlending channels. However, these problems were created by individuals who failed in their moral duties when making decisions that later led to significant harmful consequences from default and bankruptcy and all the way to suicide (Gilbert 2011;Richards et al 2008).…”
Section: Ethical Considerations In Crowdlendingmentioning
confidence: 99%
“…The report also found that details given by applicants were not verified in 9 out of 10 applications. All of this could leave the lender with an unclear picture of the customers' ability to service debt and result in lenders issuing credit limits, which are far beyond the cardholders' annual earnings or affordability (Richards et al, 2008). According to Cattermole (2004), this resulted in a drastic increase in bad debt being written off since 2000.…”
Section: Reckless Lendingmentioning
confidence: 99%
“…(Debt collection agent 4) … cos we do have also clients that come in that for instance go into the bank for a £500 overdraft just to help them out and they are offered £5,000 loan so we do have a number of clients that state that the loans and credit cards were too easily available or it wasn't explained enough. (CAB advisor 1) It is our contention that this is not just a problematic side effect of a loosening of government control over credit through deregulation (Richards, Palmer, & Bogdanova, 2008), but a deliberate strategy through which to cultivate revolving debtors in a securitized industry where profits are contingent on a steady stream of persistent revolving debtors (Montgomerie, 2007). However, for organizations predicated on the establishment of revolving debts it forms a careful operational strategy.…”
Section: Parasitic Lending: Establishing the Relationship With The Hostmentioning
confidence: 99%
“…However, for organizations predicated on the establishment of revolving debts it forms a careful operational strategy. According to Richards et al (2008) this also means that people living in poverty in the UK pay in excess of £500 million a year in excessive interest charges.…”
Section: Parasitic Lending: Establishing the Relationship With The Hostmentioning
confidence: 99%